Implementation of AI Chatbot as an Interactive Learning Medium on Accounting Lessons in SMK - Tulus Khairunisa; Suyatmini Suyatmini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The purpose of this research is to describe how the implementation of AI-based accounting learning Chatbot as well as any obstacles faced by teachers in class X SMK Batik 1 Surakarta major Financial Accounting and Institutions (AKL). This type of research is qualitative by using case study methods against students who will use AI Chatbot on accounting subjects. Research was conducted at SMK Batik 1 Surakarta. The subjects in this study are X-grade students and teachers in financial and institutional accounting. (AKL). Primary data is obtained from students who are going to use the Chatbot AI application and secondary data from previous research as a journal that matches the research topic. Data analysis techniques include data collection, data presentation, data reduction, and conclusion drawings. In this implementation effectively enhance the understanding and skills of students and teachers in the use of artificial intelligence technology. The use of AI Chatbot has the potential to enhance student engagement and expand the availability of diverse learning materials, while also facilitating the development of problem-solving and analytical skills among students. However, obstacles such as inadequate understanding, resource constraints, and effective integration into the learning process must be overcome. Given these issues, it is vital to build long-term collaboration and provide sustainable assistance between educational foundations, formal education institutions, and government agencies.